(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
In this paper Complete Decomposition Model is used to compute the future energy saving pattern from the difference of the ’trend’ and ’real’ values of energy consumption. The ’trend’ is defined as a sum of activity effect and the energy use in the base year. The ’real’ is defined as a sum of energy consumption in the base year and the change in energy consumption due to the activity effect, structural effect and intensity effect. This analysis is carried out in respect of Bangladesh for the period 2008-2030. The economic sectors that are taken in to account are agriculture, industry and service. The futuristic view shows that Bangladesh can save about 47.47 MTOE in agriculture sector and 34.96 MTOE from service sector. On the other hand, industry sector, which is accounted for 58% of the total energy consumption, failed to save energy, rather the country consumed 227 MTOE more energy than usual. The energy rebound effect that relies upon the activity effect and structural effect has also been estimated to examine the energy uses pattern of these sectors. The aggregate energy rebound effect was found to be 1480 MTOE, of which activity effect and structural effect contribute 91.21% and 8.78% respectively. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13066 Bangladesh J. Sci. Ind. Res. 47(3), 313-320 2012